Electronic polymers in lipid membranes - Johansson, Patrik K. (Sci Rep, 2015)
Electrical interfaces between biological cells and man-made electrical devices exist in many forms, but it remains a challenge to bridge the different mechanical and chemical environments of electronic conductors (metals, semiconductors) and biosystems. Here we demonstrate soft electrical interfaces, by integrating the metallic polymer PEDOT-S into lipid membranes. By preparing complexes between alkyl-ammonium salts and PEDOT-S we were able to integrate PEDOT-S into both liposomes and in lipid bilayers on solid surfaces. This is a step towards efficient electronic conduction within lipid membranes. We also demonstrate that the PEDOT-S@alkyl-ammonium:lipid hybrid structures created in this work affect ion channels in the membrane of Xenopus oocytes, which shows the possibility to access and control cell membrane structures with conductive polyelectrolytes.